On the Relationship between Winter Sea Ice and Summer Atmospheric Circulation over Eurasia - Wu, Bingyi; Zhang, Renhe; D’Arrigo, Rosanne; Su, Jingzhi (Journal of climate, 2013)
Using NCEP–NCAR reanalysis and Japanese 25-yr Reanalysis (JRA-25) data, this paper investigates the association between winter sea ice concentration (SIC) in Baffin Bay southward to the eastern coast of Newfoundland, and the ensuing summer atmospheric circulation over the mid- to high latitudes of Eurasia. It is found that winter SIC anomalies are significantly correlated with the ensuing summer 500-hPa height anomalies that dynamically correspond to the Eurasian pattern of 850-hPa wind variability and significantly influence summer rainfall variability over northern Eurasia. Spring atmospheric circulation anomalies south of Newfoundland, associated with persistent winter–spring SIC and a horseshoe-like pattern of sea surface temperature (SST) anomalies in the North Atlantic, act as a bridge linking winter SIC and the ensuing summer atmospheric circulation anomalies over northern Eurasia. Indeed, this study only reveals the association based on observations and simple simulation experiments with SIC forcing. The more precise mechanism for this linkage needs to be addressed in future work using numerical simulations with SIC and SST as the external forcings. The results herein have the following implication: Winter SIC west of Greenland is a possible precursor for summer atmospheric circulation and rainfall anomalies over northern Eurasia.